Comparative study of direct and indirect techniques in anterior rehabilitation (Research, Society and Development, 2022)
The harmonious and aesthetically pleasing smile is the main target of patients in dental offices today. The professional must carry out the diagnosis and treatment plan according to the patient's wishes. Thus, aesthetic problems that involve morphological changes should prioritize conservative treatments. In this context, veneers are, in general, the first therapeutic option, leaving the choice of material, which can be porcelain or composite resin, at the discretion. Thus, the objective of this study is to verify the difference between composite resin veneers and porcelain veneers in rehabilitation of aesthetic treatments. To this end, a bibliographic search was carried out in databases such as Pubmed, Scielo and Google Scholar, for articles of relevance to the study. The aesthetic restoration of anterior teeth is considered a great challenge for Restorative Dentistry, expanding the indication of porcelain veneers for this type of procedure. Through this technique, problems with color, shape, size and position of teeth can be solved without major damage to the dental structure, in addition to having good durability. Through resin composites it is possible to obtain a result similar to the dental structure, with a clinical work considered fast and effective, depending on the professional's skill. Adequate planning is a fundamental step for clinical success, and the patient should be informed about the procedures to be performed. It is up to the professional to evaluate and select the appropriate material for the patient.